The forbidden Greek - Smart, Michelle (Smart, Michelle. Greek Groom Swap, 2024)
When the Greek billionaire is isolated with the last woman he should ever want, it’s only a matter of time until their chemistry combusts… Enjoy this powerful forbidden, forced-proximity romance by Michelle Smart. He wants… what he can’t have. The last person Greek billionaire Leander Liassidis wants to see is Kate Hawkins. He even abandoned his convenient wedding to escape his forbidden attraction to her. She’s infuriating, irresistible…and on the doorstep of his Californian mansion! Maid of honor Kate knows she’ll have her work cut out for her bringing Leander back to the altar. She doesn’t expect the need blazing in his gaze—or the explosive connection it ignites. Kate knows that giving in to their desire would be unforgivable. But could she ever forgive herself if she walked away from a bond this powerful?